Study of Germination and Seedling Growth of Piper guineense - Ezenu, Vivian Njideka; Akinropo, Michael Seun; Sakpere, Ayobola Moninuola Abosede (Journal of Tropical Crop Science, 2024)
Natural regeneration of black pepper (Piper guineense Schumach and Thonn) through seeds is poor and cultivation by local farmers is very limited since it is usually collected from the wild. High demand has put a pressure on its population in our declining forests and a call for domestication of non-timber forest plant species is ongoing. This study identified germination requirements, germination characteristics and seedling growth of Piper guineense with a view to providing information on its propagation from seeds. There were two major pre-sowing treatments - Fresh or dry fruits or seeds. Germination and seedling growth parameters were measured for all treatments. Results showed that Piper guineense seeds undergo epigeal germination, the radicle developing into three-legged hairy rootlets. The highest percentage germination, germination rate and germination index were recorded in the treatment with fresh seeds planted in petri dish. The dry seeds and fruits recorded no germination even after 38 days of planting. For seedling growth, the developing leaves have a higher sink strength between the fourth and fifth month of development and this stage may be crucial to the growth of the seedling. Piper guineense seeds must be sown fresh for germination to take place.